Переменный режим эксплуатации системы глубокой утилизации теплоты уходящих из котла газов - Ефимов, Александр Вячеславович; Гончаренко, Александр Леонидович; Касилов, Олег Викторович; Гончаренко, Леонид Васильевич (НТУ "ХПИ", 2015)
С помощью расчетного исследования, выполненного на базе разработанной компьютерной программы, осуществлена оценка переменного режима эксплуатации системы глубокой утилизации теплоты уходящих из котла газов. В качестве объекта исследования рассмотрен один из вариантов теплоутилизационной системы замкнутого типа, в состав которой входят паровой котел Е-1,0-09 Г3 и конденсационный теплообменный аппарат поверхностного типа, предназначенный для нагрева сетевой воды системы горячего водоснабжения.

The design investigation was carried out to determine the variable mode of the operation of the system intended for the in-depth utilization of the heat of gases effluent from the boiler. The investigation was carried out using the computer program developed by the authors. As a test subject we used one of the options of the system of a closed type that includes the boiler with the steam capacity of 0,278 kg/s and the condensation heat exchanger of a surface type intended for the heating of the delivery water in the hot water supply system. The natural gas is popped in the boiler. To protect the gas flue pass from corrosion and the damage the by-pass was arranged by the heat exchanger to increase the temperature of effluent gases above the dew point. At a nominal load when the fuel consumption is kept at a constant level the condensation portion of the heat exchanger can heat 0,39445 kg/s of water in the temperature range of 10 C to 49 C with a further increase in its temperature to 80,4 C in the condensation-free portion. The computational investigation showed that the decrease in the loading by 40 % results in the decrease of water consumption to 0,1948 kg/s, actually by a factor of two. The water heating temperature also drops to 68,1 C. However, the heat exchange surface is enlarged, and it serves as a surface for the condensation of the water vapor of furnace gases cooled to the temperature of 35 C and the appropriate reduction of the condensation–free surface is observed. Interesting data on a change of thermal physical characteristics along the heat-exchange surface of the condensation portion of the unit were also obtained changing the operation modes of the system.
A variable mode of the operation of the system designed for the in-depth utilization of the heat of gases effluent from the boiler
Keywords: энергосбережение; уходящие дымовые газы; конденсационный теплообменный аппарат; коэффициент теплопередачи; коэффициент массоотдачи; varying type of duty; effluent flue gases; efficiency factor; heat transfer coefficient; mass transfer coefficient